Change in lumen eccentricity and asymmetry after treatment with Absorb bioresorbable vascular scaffolds in the ABSORB cohort B trial: A five-year serial optical coherence tomography imaging study - Suwannasom P. (2017)
© Europa Digital & Publishing 2017. All rights reserved. Aims: The aim of the study was to investigate long-term changes in lumen eccentricity and asymmetry at five years after implantation of the Absorb bioresorbable vascular scaffold (BVS). Methods and results: Out of 101 patients from the ABSORB cohort B trial, 28 patients (29 lesions) with serial optical coherence tomography (OCT) examination at four different time points (cohort B1: postprocedure, six months, two, and five years [n=13]; cohort B2: post-procedure, one, three, and five years [n=16] ) were evaluated. The longitudinal variance in lumen diameter was assessed by asymmetry index (AI). An asymmetric lesion was defined as AI > 0.3. The circularity of the lumen or scaffold was evaluated by the eccentricity index calculated as minimal divided by maximal luminal or scaffold diameter per cross-section. The lowest lumen eccentricity index within a scaffold segment (EIL) < 0.7 was defined as an eccentric lesion. Post procedure, an eccentric lesion was observed in 72.4% and became concentric in 93.1% at five years (post EIL 0.67±0.05 vs. five-year EIL 0.80±0.10, p=0.03) with a modest reduction of the lumen area from baseline to five years by 0.75±0.32 mm2. Asymmetric lumen morphology was observed in 93.1% (n=27) post implantation and persisted until five-year follow-up. On serial OCT analyses, there was a substantial increase in the scaffold EI during the first two years (post 0.70±0.06, six months 0.76±0.08, two years 0.85±0.07); then, it remained stable whereas the lumen circularity improved further. There were no significant differences in major adverse cardiac events regarding the lumen morphology over the fiveyear follow-up. Conclusions: In patients treated with the Absorb BVS, the cross-sectional circularity improved over five years while the variance in longitudinal diameters remained. Regaining of lumen circularity is mainly caused by reshaping of the scaffold during the first two years.